Determinants of Innovative Behavior: A Path Model of Individual Innovation in the Workplace - Scott, Susanne G.; Bruce, Reginald A. (Academy of Management Journal, 1994)
The present study integrated a number of streams of research on the antecedents of innovation to develop and test a model of individual innovative behavior. Hypothesizing that leadership, individual problem-solving style, and work group relations affect innovative behavior directly and indirectly through their influence on perceptions of the climate for innovation, we used structural equation analysis to test the parameters of the proposed model simultaneously and also explored the moderating effect of task characteristics. The model explained approximately 37 percent of the variance in innovative behavior. Task type moderated the relationship between leader role expectations and innovative behavior.